Stature Estimation Using Hand and Handprint Dimensions Among Malaysian Population - Atirah G, Nur; M, Khairulmazidah (International Journal of Engineering and Technology, 2018)
There are various studies of stature estimation which is very important for formulation of biological profile and is population specific. This study was conducted to estimate height using hand and handprint dimensions among Malaysian population. This study comprises 200 voluntary male and 200 voluntary female subjects with age ranging from 20 to 60 years. Eight anthropometric measurements were taken on each hand and its corresponding prints. All the data was statistically analyzed using IBM SPSS Statistic 19 software. The result indicated that hand length and handprint length has the strongest correlation with stature for male and female subjects. However, for unknown gender, it was showed that almost all of the hand dimensions measured in this study except for pinky finger length showed strong correlation with stature for both right and left hand while for handprint measurements, only hand length and palm length gave better correlation with stature. Formulae for stature estimation using various hand and handprint dimensions were derived successfully for both linear and multiple regression for the ease of data availability in future use.Â Â Â